The Role of Islam in Peaceful Coexistence (Analytical study by the Sirah of the Holy Prophet Muhammadﷺ) - Shahzad , Amir; Azam, Hafiz Zaheer; Ullah, Dr. Anwar (Al-Amīr Research Journal for Islamic Studies, 2024)
Islam teaches us about peace and harmony and peaceful co-existence not only with Muslims even with all the people of the different religions. While adopting Islam, it is a major duty of every Muslim to maintain positive relations with the people of other religions on the basis of peace, love, and harmony and on the basis of brotherhood, here it is not a matter that from which religion he/she belongs, because by doing so, it will be possible to overcome the war of bigotry and extremism in the world. But some western scholars have tried to change the teaching structure of the Holy Qur’an and Hadith of Prophet Muhammad ﷺand have tried to damage the truth picture of Islamic teachings towards the love, and harmony with other religions. In this article we will explain how Islam emphasizes peaceful coexistence and strong interfaith relations with other religions. I have adopted modern research methods in this article and tried to prove that how peaceful coexistence has importance in Islam. So here our aim will not be to merely quote words, but we will honestly embellish our research with references. Key Words: Islam, Peaceful, Muhammad, Analytical, Religions, Coexistence, Muhammad’s (ﷺ) Biography.